Do climate-smart agricultural practices support adaptation, mitigation and productivity? A review of CSA practices used in participatory video interventions in India, Kenya, and Uganda - Welk, Lukas (International Food Policy Research Institute, 2023)
Climate change poses a threat to smallholder farmers worldwide, impacting livelihoods and agricultural pro duction. At the same time, agrifood systems account for about one-third of all greenhouse gas (GHG) emissions. Climate-smart agriculture (CSA) offers synergistic practices that boost productivity, aid farmers in adapting to cli mate change, and have the potential to mitigate GHG emissions. This note reviews the extent to which a set of practices identified by smallholder farmers in India, Kenya, and Uganda for inclusion in a participatory video-based extension intervention meet the CSA criteria. The findings suggest that the practices hold triple-win potential but often several need to be applied as a package; they also need to be adapted to local conditions.